CRM Strategies In MSC Status Companies - Zafar, Mohammad Afnan (2007)
The aim of this study is to investigate the current situation of overall CRM strategies and CRM usability and success or failure cases and the main reasons for failure among the Malaysian market based on the MSc status companies with comparison with the global status of the CRM systems.